Screening, brief intervention, and referral to treatment (SBIRT) curriculum integration and sustainability: Social work and nursing faculty perspectives. Issue 2 (3rd April 2018) - Belfiore, M. Nicole; Blinka, Marcela D.; BrintzenhofeSzoc, Karlynn; Shields, Joseph
ABSTRACT: Background. The Substance Abuse and Mental Health Services Administration (SAMHSA) has funded grants to universities to provide training and conduct research on the dissemination of Screening, Brief Intervention, and Referral to Treatment (SBIRT) to health care professionals. However, when it comes to integrating SBIRT content into an existing curriculum, difficulties can arise. When there is so much content already in the curriculum, adding more can be challenging. Additionally, some faculty believe that course curricula should be driven by the expertise and knowledge of faculty, not by opportunities afforded because of grant funding. Methods. Using qualitative semi-structured faculty interviews and thematic data analysis, this study explored the process and content issues surrounding the integration of SBIRT content into the Masters of Social Work (MSW) and Masters of Science in Nursing (MSN) curricula at one university. Results. Guidelines for the successful integration of SBIRT content into MSW and MSN curricula fall into two thematic areas: 1. Encourage buy-in and ownership of SBIRT curriculum development by current faculty. 2. Use a scaffolded approach. SBIRT includes several unique content areas which should be integrated per competencies addressed in each course. SBIRT content areas lend themselves to integration into a range of courses, employing an array of learning techniques and teaching materials. Scaffolding content requires creativity, which serves as the basis of the six subthemes that guide a scaffolded SBIRT integration approach. Conclusions . SBIRT offers an evidence based intervention that uses a public health approach to reduce harm from substance use. As such, professional nursing and social work education programs should teach SBIRT to their master's level practitioners. This paper proposes guidelines for integrating that content into existing curricula.